Implementation of the Bangga Kencana Program (Family Development, Population and Family Planning) in Population Control Efforts in East Java Province - Lilin, Lilin Rohmawati (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract High population growth in East Java causes social and economic problems, such as poverty and unemployment. The Bangga Kencana program aims to reduce birth rates and create quality families to support sustainable development. This research analyzes program implementation using the theory put forward by Edward III using descriptive qualitative research methods. The research results show that effective communication between the government, BKKBN, and the community, as well as the use of social media, supports the success of the program. This program is supported by an organized work team, adequate budget, and highly committed implementers. A good bureaucratic structure as well as the implementation of SOPs and digital technology also facilitate program implementation. Keywords: Bangga Kencana, Family Planning, Population Control